Medical Procedure Problems from the Viewpoint of Elderly Referrals to Healthcare Centers of Hamadan: A Qualitative Study - Parisa Parsa; Forouzan Rezapur-Shahkolai; Maliheh Araghchian; Maryam Afshari; Alireza Moradi (Sālmand, 2017)
Objectives Increasing age is associated with the risk of diseases and increased treatment problems. Due to the aging population and the need for consumption of drugs for chronic diseases of the elderly, understanding health challenges and treatment problems in the elderly is important. Based on this, a qualitative study was performed to identify treatment problems in older people's viewpoint in Hamadan . Methods & Materials This qualitative study was conducted by content analysis approach. Data were collected through semi-structured propound interview with 15 elderly people having an age average of 66.47±4.47 years, who were referred to health centers in Hamadan city in 2015. Data was gathered by sampling based sexes with a maximum variation of age range of 60 to 75 years, socioeconomic status, and educational level. All interviews were simultaneously handwritten. Data were analyzed using content analysis method. Data strength was confirmed by participants and researchers. Results Elderly patients had an average age of 66.47 years and a standard deviation of 4.47. Of the 15 participants, there were 6 females and 9 males. Data analysis resulted in extraction of 3 main themes "causes related to doctors, taking medication problems and shortage of drugs."These themes were determined by the following eleven subthemes: "the cost of visits to doctors, distrust of doctors, doctors not caring for the elderly, complications for the elderly, early completion medicines , efficacy, the absence of an alternative drug for existing drugs, many drugs for consumption, use of other drugs, lack of medicines in some pharmacies, and delivery of expired drugs to the elderly in some pharmacies". Conclusion The results showed that there are problems of treatment in elderly. So after reviewing the problems with appropriate interventions, training can guide and help the elderly in this area. The authorities can also use findings from research in planning.